Biotecnologias agrícolas e sociedade: disputas sociais e regulamentação dos transgênicos no Brasil (1985 2005) - Warpechowski, Eduardo Moraes (2010)
In this dissertation we present an historical panorama of the introduction of genetically modified organisms (transgenics) in Brazil, its repercussion and the social debate about several controverse aspects of this new technological product. In front of every group s view, we argued regarding the ambiguous centrality of technology at the contemporaneous world, presenting the possible reasons of lengthy divergence among the several agents involved in. One central subject guides this research: why the genetically modified seeds still nowadays didn t have a satisfactory and definitive legal resolution in Brazil, in the meaning of regard the demands indicated by the civil groups? This debate was polarized between two groups whom not very dialog for don t agree with the opposed argumentations to their stands. In one hand, we had the genetically modified seeds defenders, like a part of the rural producers, the farming industry, the scientists connected to biotechnological research centers, speaking by the science and the national economics and developmental interests. On the other hand, we have the environmentalists, non-governmentalist organizations and civil groups defending a science s ethical posture, sustainable ecological practices, the small producers and the consumers rights. In the midst of the contest, the Brazilian government has manifested contradictory trying to conduce this political state of affairs mediating these several interests on dispute.